Pursuing Hegemonic Masculinity Through Violence: An Examination of Anti-Homeless Bias Homicides. Issue 13 (July 2021) - Allison, Kayla; Klein, Brent R.
The purpose of this study is to examine the ways in which general strain and masculinity theories combine to offer explanations for why and how some offenders commit fatal attacks against persons who are homeless. Specifically, the authors ask, how does "strained masculinity" explain why and how offenders commit fatal bias attacks of violence against homeless persons? The authors conceptualize hegemonic masculinity as a positively valued goal that men continuously work to achieve or demonstrate and theorize that bias crime offenders use violence against persons who are homeless as a way to address challenges or strains in their pursuit of hegemonic masculinity. To overcome issues with official bias crime data, the current study utilizes data on anti-homeless homicides from the U.S. Extremist Crime Database (ECDB), which is an open-source database with information on incident-, offender-, and victim-level characteristics of bias homicides. The authors rely on a homicide narrative approach to conduct in-depth analyses of anti-homeless homicide events to assess how these fatal transactions situationally unfold. Three categories related to strained masculinity emerged from a thematic analysis of anti-homeless homicide narratives. In particular, men engaged in acts of violence against the homeless as responses to challenges to masculinity and to pursue hegemonic masculinity through alternative avenues, including violence as a "sport" and violence used to reclaim control of public spaces. Overall, findings demonstrate the utility of a strained masculinity framework for explaining anti-homeless homicides and contribute to the important task of integrating criminological and sociological theories for explaining incidents of bias crime.